17. THE EVALUATION ON THE PERFORMANCE OF WAQF LAND MANAGEMENT IN THE STATE OF SELANGOR - Anuar, Nur Afiqah; Zazali, Nurashikin; Sulaiman, Muhammad Azwan; Kaspin @ Saribin, Sr Morni (Journal of Islamic, Social, Economics and Development, 2024)
Apparently, many people especially Muslims believe that waqf is solely for religious matters and have less awareness of what benefits they could gain from waqf land activities. Hence, the concept of waqf must be explained and fulfilled by the organization appointed as a trustee, such as State Islamic Religious Councils. Many researchers have highlighted the issues and challenges faced in waqf practice especially on ineffective administration of waqf land due to improper provisions available. Therefore, this paper aims to evaluate the performance of waqf land management in Selangor. A qualitative method is adopted in this research through interview sessions with expertise and Selangor Waqf Corporation has been chosen as the case study. The elements of employee performance, management accountability, management effectiveness, and efficiency are evaluated to understand the current performance of waqf land management in Selangor. The research shows that the overall performance of waqf land management in Selangor is on good terms. The rental collection on waqf properties developed is also increasing despite the pandemic crisis hit a few years back. Therefore, evaluating the performance of waqf land management gives Selangor Waqf Corporation an idea of what aspects they can improve and upgrade to maintain their managerial service to the top tier, especially in this modern and digitalized era.